Administrative-legal system of the ottoman empire. (Journal of Oriental Studies, 2016)
In the article examined the questions related to politics of the Ottoman empire.And similarly the article is sanctified to the problem of functioning of the administrative-legal system of the Ottoman empire.
Keywords: Ottoman empire; eve; sheriat; raya; court kadi